The Urgent Need for Mathematics Learning Innovation in the Era of Society 5.0 - Surya Adi Saputra; Deny Hadi Siswanto; Handika Suryatama (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
Education and the Society 5.0 era are interconnected through technological advancements that influence the role of teachers, teaching methods, mindsets, and educational media, particularly in mathematics education. The purpose of this study is to analyze the implementation and impact of technology in mathematics education in the Society 5.0 era. This study uses a qualitative approach with a literature review design to collect, analyze, and disseminate previous research related to the topic. The findings highlight several pioneers in mathematics education in the Society 5.0 era, such as the importance of integrating technology, technology-based learning approaches, technological tools in mathematics education, digital collaboration and communication, interactive technology, and real-time learning technology. Furthermore, both positive and negative impacts of implementing these technologies were found. Based on the research results, it is recommended that educational institutions integrate technology into mathematics education through teacher training, providing supporting infrastructure, and designing curricula that align with these advancements to enhance the effectiveness, efficiency, and problem-solving skills of students in facing the challenges of the Society 5.0 era.